2006
DOI: 10.1111/j.1442-2042.2006.01600.x
|View full text |Cite
|
Sign up to set email alerts
|

Case of carcinosarcoma of urinary bladder obtained a pathologically complete response by neoadjuvant chemoradiotherapy

Abstract: Carcinosarcoma of the bladder is an unusual malignancy characterized by an intimate admixture of malignant epithelial elements (carcinoma) and malignant soft tissue elements (sarcoma). To our knowledge, almost 80 cases have been reported, usually as case reports or small series. Patient with carcinosarcoma usually present with a high stage malignancy. Cystectomy or transurethral resection is the preferred treatment, often followed by radiation therapy, although prognosis is very bad. We herein report a case of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…Radiotherapy or chemotherapy has yielded conflicting results. Neoadjuvant/adjuvant radiochemotherapy has been used in many cases, and there were complete responses after neoadjuvant treatment [12]. Tazi et al reported that neoadjuvant radiochemotherapy with radical cystectomy was provided 20 months of recurrence-free survival [13].…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy or chemotherapy has yielded conflicting results. Neoadjuvant/adjuvant radiochemotherapy has been used in many cases, and there were complete responses after neoadjuvant treatment [12]. Tazi et al reported that neoadjuvant radiochemotherapy with radical cystectomy was provided 20 months of recurrence-free survival [13].…”
Section: Discussionmentioning
confidence: 99%
“…There is no standard radiotherapy or chemotherapy regimen although response to cisplatin and gemcitabine has been observed in some cases. 21 Although radical surgery is recommended, local recurrence and/or metastases frequently occur after surgical resection, and in 8 cases of CS of the upper urinary tract, median survival after surgical resection was only 8.2 months. 1 Metastases of CS usually have a mixed histology, with epithelial predominance.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the patients in the SEER study received either TURB only (54.9%), cystectomy (35.7%) or surgery combined with radiation therapy (15.8%). [2] Hoshi et al [3] presented a patient with bladder carcinosarcoma who achieved a complete response after neoadjuvant radiochemotherapy. Therefore, we applied this protocol to our patient and obtained the same result; our patient was disease-free 20 months after the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Immunohistochemistry is mandatory for diagnosis, and ideal treatment includes radical surgery and chemoradiotherapy. [3] This paper examined the clinical, therapeutic and histological features of this rare tumor following an observation of carcinosarcoma in the urinary bladder.…”
Section: Introductionmentioning
confidence: 99%